105 COVID-19 IN OLDER ADULTS: INPATIENT OUTCOMES IN A LEVEL 3 IRISH HOSPITAL. (18th November 2021) - Young, C; Moore, M; Gyenes, M; Sheehan, O; Ahmed, S
Abstract: Background: COVID-19 has proved devastating in older persons. Previous studies reveal a mortality rate of 31% for hospitalised patients over 70. 1 We examine outcomes for older COVID patients in our hospital. Methods: We conducted a Hospital In Patient Enquiry Scheme review for patients coded as COVID-19 between 19/03/2020–19/02/2021 (n = 674). Older adults were defined as those aged over 65 years at time of admission. Age, sex, length of stay and survival were collected. Data was collated by 'wave': (Wave 1 n = 294, 2 n = 105, 3 n = 275). We reviewed whether patients had a CT pulmonary angiogram (CTPA) on the National Integrated Medical Imaging System. Results: 42.3% of COVID patients in our hospital were older persons (n = 285). This remained stable throughout the pandemic (Wave 1 44.2%, Wave 2 44.7%, Wave 3 39.3%). Mean length of stay was 19.7 days for older adults vs 7.4 for those under 65. Older persons had a higher mortality rate at 30.9% vs 3.6%. Overall incidence of PE was low at 1.9% (1.1% in older persons). However, the likelihood of a CTPA being positive for those over 65 was much higher at 42.9% vs 17.9%. While there was improvement in mortality rates in older persons from Wave 1 (31.5%) to 2 (19.1%), our data showed a significant rise in mortality in Wave 3 (35.2%). This compares to a different pattern in younger people, with mortality rates by wave at 6.7%, 0% and 1.7%. Conclusion: In a large Irish cohort of patients hospitalised with COVID-19, 42.3% were older adults. Length of hospital stay was 3 times longer and mortality was 10 times higher than patients under 65. Older adults were also more likely to have a positive CTPA. Further study is needed to evaluate the long term effects of COVID-19 in our older population. Reference: Zerah et al, Journals of Gerontology. Series A, Biological Sciences and Medical Sciences. 2021 Feb 25; 76 (3): e4–e12.